Chromatin remodeling inactivates activity genes and regulates neural coding - Yang, Yue; Yamada, Tomoko; Hill, Kelly K; Hemberg, Martin; Reddy, Naveen C; Cho, Ha Y; Guthrie, Arden N; Oldenborg, Anna; Heiney, Shane A; Ohmae, Shogo; Medina, Javier F; Holy, Timothy E; et al. (Science (American Association for the Advancement of Science), 2016)
Activity-dependent transcription influences neuronal connectivity, but the roles and mechanisms of inactivation of activity-dependent genes have remained poorly understood. Genome-wide analyses in the mouse cerebellum revealed that the nucleosome remodeling and deacetylase (NuRD) complex deposits the histone variant H2A.z at promoters of activity-dependent genes, thereby triggering their inactivation. Purification of translating messenger RNAs from synchronously developing granule neurons (Sync-TRAP) showed that conditional knockout of the core NuRD subunit Chd4 impairs inactivation of activity-dependent genes when neurons undergo dendrite pruning. Chd4 knockout or expression of NuRD-regulated activity genes impairs dendrite pruning. Imaging of behaving mice revealed hyperresponsivity of granule neurons to sensorimotor stimuli upon Chd4 knockout. Our findings define an epigenetic mechanism that inactivates activity-dependent transcription and regulates dendrite patterning and sensorimotor encoding in the brain.